Low body fat percentage and menstrual cycle disorders in female elite adolescent dancers - Liu, Z.; Gong, Y.; Nagamoto, H.; Okunuki, T.; Yamaguchi, R.; Kobayashi, Y.; Li, Y.; Maemichi, T.; Kumai, T. (Journal of Dance Medicine & Science, 2024)
Introduction The menstrual cycle is an important indicator of health in female athletes. Female elite adolescent dancers are expected to control their weight while also training intensely, which can lead to menstrual disorders. This study aimed to investigate the relationship between body composition and menstrual status in female elite adolescent dancers.